Definicja kognitywna jako narzędzie opisu emocji negatywnych w językach rosyjskim i ukraińskim (na przykładzie emocji strachu) - Małecki, Łukasz (Acta Polono-Ruthenica, 2018)
Emotions in human consciousness take form of emotional concepts, described by means of such features as traditions, customs, special stereotypes of thinking, beh avior models, etc. The present article attempts to analyse the linguistic realization of the concept of „fear” in Russian and Ukrainian languages. The language analyze is based on the purposes of the cognitive definition.